APLIKASI TEGANGAN-REGANGAN EKIVALEN PADA PERHITUNGAN UMUR FATIK PADUAN AL 6063 UNTUK BEBAN AKSIAL DAN TORSI - Suhartono, H. Agus (MESIN, 2007)
Tension-compression and torsion low cycle fatigue testing were conducted by straincontrol on Aluminum alloy 6063 thin wall tube specimens. The relation between type of loading anddeformation characteristics were recordedand analyzedfor calculating equivalent stress and strain.The Von Misses and Henckys equation can transform the shear stress-strain into equivalent stressstrainvery good which is proved by experimental result. The life prediction based on the calculatedequivalent straingive a satisfactory resultfor both type of loading.